Prenatal Diagnosis of Osteogenesis Imperfecta - Özyüncü, Özgür; Yapıcı, Zuhal; Altınok, Gülçin; Beksaç, Sinan (Gynecology Obstetrics & Reproductive Medicine, 2010)
Skeletal dysplasias are a group of diseases with a wide spectrum related to bone and cartilage. Some forms are lethal whereas some forms have milder clinical progression. Prenatal diagnosis of skeletal dysplasias may be possible especially when there is an index case in the family. Ultrasonography plays the central role in prenatal diagnosis and most common sonographic features are angulation of long bones, bending of femur or bowing signin the long bones. We present a case whose follow up for fetal short extremities ended with termination of pregnancy. The differential diagnosis is hard and depend especially on the fetal x-ray. Final diagnosis was lethal type osteogenesis imperfecta.